Galectin-3 Decreases 4-1BBL Bioactivity by Crosslinking Soluble and Membrane Expressed 4-1BB - Nielsen, Morten Aagaard; Juul-Madsen, Kristian; Stegmayr, John; Gao, Chao; Mehta, Akul Y.; Greisen, Stinne Ravn; Kragstrup, Tue Wenzel; Hvid, Malene; Vorup-Jensen, Thomas; Cummings, Richard D.; Leffler, Hakon; Deleuran, Bent Winding (Frontiers in Immunology, 2022)
4-1BB is a T cell costimulatory receptor and a member of the tumor necrosis factor receptor superfamily. Here, we show that Galectin-3 (Gal-3) decreases the cellular response to its ligand (4-1BBL). Gal-3 binds to both soluble 4-1BB (s4-1BB) and membrane-bound 4-1BB (mem4-1BB), without blocking co-binding of 4-1BBL. In plasma, we detected complexes composed of 4-1BB and Gal-3 larger than 100 nm in size; these were reduced in synovial fluid from rheumatoid arthritis. Both activated 4-1BB+ T cells and 4-1BB-transfected HEK293 cells depleted these complexes from plasma, followed by increased expression of 4-1BB and Gal-3 on the cell surface. The increase was accompanied by a 4-fold decrease in TNF production by the 4-1BBhighGal-3+ T cells, after exposure to 4-1BB/Gal-3 complexes. In RA patients, complexes containing 4-1BB/Gal-3 were dramatically reduced in both plasma and SF compared with healthy plasma. These results support that Gal-3 binds to 4-1BB without blocking the co-binding of 4-1BBL. Instead, Gal-3 leads to formation of large soluble 4-1BB/Gal-3 complexes that attach to mem4-1BB on the cell surfaces, resulting in suppression of 4-1BBL’s bioactivity.